2016
DOI: 10.3399/bjgp16x683485
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two interventions on the discontinuation of benzodiazepines in long-term users: 36-month follow-up of a cluster randomised trial in primary care

Abstract: BackgroundPrimary care interventions that promote cessation of benzodiazepine (BZD) use in longterm users are effective at 1 year, but their efficacy at 3 years is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
1
46
1
3
Order By: Relevance
“…Segundo Vicens et al 13 , intervenções nos cuidados primários para promover a cessação do uso de BZDs em usuários de longo prazo são eficientes por um período de um ano, porém aos três anos ou mais de cessação ainda é incerta a eficácia da interrupção. Entre as intervenções, destacam-se orientações durante a consulta, informações prescritas sobre como parar o uso do medicamento, bem como, consultas a cada duas a três semanas, seguida de redução de dose escalonada (redução de 10 a 25% na dose diária) e intervenções mais complexas que fornecem apoio tanto psicológico como farmacológico, como a mudança de um BZDs de meia-vida curta para um de meia-vida longa.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Segundo Vicens et al 13 , intervenções nos cuidados primários para promover a cessação do uso de BZDs em usuários de longo prazo são eficientes por um período de um ano, porém aos três anos ou mais de cessação ainda é incerta a eficácia da interrupção. Entre as intervenções, destacam-se orientações durante a consulta, informações prescritas sobre como parar o uso do medicamento, bem como, consultas a cada duas a três semanas, seguida de redução de dose escalonada (redução de 10 a 25% na dose diária) e intervenções mais complexas que fornecem apoio tanto psicológico como farmacológico, como a mudança de um BZDs de meia-vida curta para um de meia-vida longa.…”
Section: Discussionunclassified
“…Pode-se também fornecer um folheto educativo explicando como melhorar a qualidade do sono para os que fazem uso de BZDs. A prática clínica centrada no paciente, na qual o médico acolhe suas expectativas e fornece explicações sobre o uso dessas medicações, suas vantagens e desvantagens, podem facilitar as decisões de como e quando iniciar ou interromper o uso 13 .…”
Section: Discussionunclassified
“…1 I have been working in a deprived area of Derby with relatively high levels of illegal drug use. Two and a half years ago the practice was prescribing benzodiazepines and Z-drugs at a level of 4% of the practice population (6500 patients).…”
Section: Discontinuation Of Benzodiazepinesmentioning
confidence: 99%
“…College Officers commenting on my article on academic general practice 1 refer to the Clinical Innovation and Research Centre (CIRC) and I agree it has achieved much in education and development. However, CIRC is not a research centre and is not seen nationally as such.…”
mentioning
confidence: 99%
“…In their study of the impact of structured support in helping people to discontinue benzodiazepines, Vicens and colleagues in Spain found that two-thirds of those who had stopped benzodiazepines at 12 months remained off them at 36 months. 5 Nic an Fhailí and colleagues explored the role of GPs in Ireland in supporting the families of those who had taken their own lives. They remind us that a minimum of six people are affected by every suicide.…”
mentioning
confidence: 99%